ANALISIS BIAYA VOLUME LABA MELALUI ALOKASI BIAYA BERSAMA SEBAGAI PERENCANAAN LABA - Wahyuni, Sri (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2012)
Wahyuni, Sri, 2012, Analysis of Cost Volume Profit through cost allocation Profit Planning Together For The Cita Rasa Company Bakery. The purpose of this study was to determine the allocation of shared cost and profit planning analysis should be done of the company. The analysis used is the analysis of BVL, which includes Contribution margin analysis, BEP and margin of safety. The least squares method to separate semi-variable costs into fixed costs and variable costs.Based on the calculation of the analysis has been done to obtain the amount of contribution margin brown bread USD 350.00 / unit, bread, jam USD 360.00 / unit, toast sesame USD 414.00 / unit, bread snow USD 286.00 / unit, raisin bread USD 413.00 / unit, banana bread USD 406.00 / unit and Donat Rp 231.00 / unit. Break even point is found to be U.S. $ 17,346,941.00 for brown bread, bread jam 25,349,794.00 USD, USD 20,011,588.00 sesame bread, buns snow USD 8,673,619.00, raisin bread Rp 13,609,900.00 ,banana bread and donuts Rp Rp 19,925,143.00 20,011,588.00. While the margin of safety obtained for 92.57% of the total product mix. Target profit of Rp 300 million a year, the sales target to be achieved by Rp 1,385,941,767.00 company with a sales target of 938,580 units in the unit.Based on the calculation above, it can be concluded that it is better Taste Bakery Bread Company uses BVL in profit planning analysis to facilitate the changes that would occur if the profit there is a change in trace element analysis BVL.. Keywords: Joint Costs, Cost Volume Profit, Profit Planning